Ventilatory ratio as a predictor for extubation failure in critical ill patients based on MIMIC-IV database (from 2008 to 2019) - Yang, Huan; Ni, Yuenan; Huang, Dong; Liang, Zongan (Frontiers in Physiology, 2023)
Background: The predictive ability of the ventilatory ratio (VR) for extubation failure risk in critically ill patients on mechanical ventilation is unclear. This study aims to examine the predictive ability of VR for extubation failure risk. Methods: This retrospective study was based on the MIMIC-IV database. The MIMIC-IV database consists of the clinical information of patients who were admitted to the intensive care unit at the Beth Israel Deaconess Medical Center between 2008 and 2019. With extubation failure as the primary outcome and in-hospital mortality as the secondary outcome, we assessed the predictive value of VR four hours before extubation using a multivariate logistic regression model. Results: Of 3569 ventilated patients who were included, the rate of extubation-failure was 12.7% and the median Sequential Organ Failure Assessment (SOFA) score was 6 before extubation. Increased VR, elevated heart rate, greater positive end-expiratory pressure, higher blood urea nitrogen level, higher platelet count, greater SOFA score, decreased pH, decreased tidal volume, presence of chronic pulmonary disease, paraplegia, and metastatic solid tumor were independent predictors for extubation failure. A threshold of 1.595 of VR was associated with prolonged intensive care unit length of stay, higher risk of mortality and extubation failure. The area under the receiver operating characteristic curve (ROC) for VR was 0.669 [0.635-0.703], which was significantly larger than the rapid shallow breathing index (0.510 [0.476-0.545]) and the partial pressure of oxygen to the fraction of inspired oxygen (0.586 [0.551-0.621]). Conclusions: VR four hours before extubation was associated with extubation failure, mortality, and prolonged length of stay in the intensive care unit. VR provides good predictive performance for extubation failure (measured by ROC) than the rapid shallow breathing index. Further prospective studies are warranted to confirm these findings.